Differences between learning model of inquiry and direct instruction toward learning outcomes on discus throw - Sinulingga, Andrew; Saputro, Deny Pradana; Nova, Andi (UIR Press, 2021)
Determining the learning model in teaching and learning activities will help students succeed, especially in physical education lessons. A Teacher is demanded to choose the right learning model according to the needs field need suitable for a pupil's characteristic. This research aims to find out determine differences between the learning model of inquiry and direct instruction on learning outcomes of discus throw. The subject of the study is students of grade ninth in State Junior High School three Pekanbaru. The research method is an experiment in which each group is fifteen students in inquiry learning models and indirect instruction models. The in research was t, the instrument discus throw, which consists of holding the discus, approaching, throwing, and following through. The T-test is an analysis technique of the data in this study by presenting two different learning groups. The result of the use of products learning outcomes of discus throwing on students of grade ninth at state junior high school three Pekanbaru by implementing inquiry learning models and direct instruction in learning of discus throw. The inquiry learning model in this study showed better results than direct instruction. The gain of students' average value contributed 13.5, whereas the average value of students in direct instruction was 12.0. Therefore, it can be concluded that the inquiry learning model is better to be implemented for the learning of physical education, especially on discus throw lesson than the implementation of direct instruction in State Junior High School three Pekanbaru.